Pengaruh metode penilaian persediaan, nilai persediaan, dan gross profit margin terhadap market value perusahaan yang terdaftar di bei tahun 2007-2009 - Ngadiman, Ngadiman; Theresia, Florence (Jurnal Akuntansi, 2011)
The title of this research "The Correlation Analysis of Inventory Valuation Method Implementation, Inventory Value, and Gross Profit margin to Manufacture Companies Market Value Listed on Indonesia Stock Exchange'', which its objective is to provide the empirical evidences about the inventory valuation method implementation, inventory value, and gross profit margin to company's market value. The object of this research is the manufacture companies which are listed os Indonesia Stock Exchange on the period of 2007-2009. Research sample was selected by using the purposive sampling and obtained 45 sample companies which are consists of 8 companies which are implementing the average inventory method and 3 7 companies are implementing the FIFO inventory method. The hypothesis testing method used the multiple linear regression method.The result of this research shows that as collectively the inventory valuation method, inventory value, and gross profit margin significantly affected the market value. And as individually, the variable that significantly affects the market value is just inventory value while inventory valuation method and gross profit margin have no significant influence to the market value.